(untitled) (Research, Society and Development, 2022)
Objective: To compare body movements between honest and false discourses. Method: A quantitative and transversal study, with descriptive and analytical approaches, performed with 40 subjects equally distributed in two groups regarding sex. The participants did not present evidences of deficiency (auditory, visual, physical or neuromotor), they remained with the hair fixed and seated during the filming of the narrative of the true and false speeches, being interpreted previously the basic movements of each subject. The obtained data were analyzed, compared and submitted to the statistical analysis in the SPSS program using the univariate and bivariate techniques and the Chi-square and Fisher Exact tests, with significance level p <0.05. Study approved by the Ethics Committee. Results: The main body alterations identified in the false speech that differed from the true one in the descriptive analysis were: tension in orbicular (increase of 35%), moderate movement of the upper limbs (increase of 30%), deep breathing (increase of 20%), (10% increase) and moderate movement (increase of 10%) and elevation of the lower limbs (increase of 10%), but without statistical evidence of association with the type of speech . In the modification of posture (increase of 15%), perceived by head or trunk movement, there was a statistically significant association to false speech (p = 0.007). Conclusion: During the production of lying speeches there was a tendency to change the body movement, having as main trigger point the postural alteration.